2023
DOI: 10.7759/cureus.35945
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Co-occurrence of Monkeypox Encephalitis and Neurosyphilis

Abstract: Monkeypox (MPOX according to the Centers for Disease Control and Prevention) has been a disease of interest in populations with high-risk sexual behavior. As sporadic outbreaks of MPOX have led to a worldwide spread, it has been declared a public health emergency by the World Health Organization. Here, we describe the case of a 44-year-old male with high-risk sexual behavior who presented with typical rashes of MPOX and altered mental status. MPOX polymerase chain reaction from the skin lesion and cerebrospina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In the majority of severe cases, patients present with neuropsychiatric complications including seizures, confusion, and encephalitis, indicating that MPXV is able to invade the central nervous system (CNS) 7,10,[12][13][14][15] . Despite its severe manifestations, the underlying neuropathogenesis of mpox is unknown, and the susceptibility of different CNS cell types to MPXV infection has not been characterised.…”
Section: Main Textmentioning
confidence: 99%
“…In the majority of severe cases, patients present with neuropsychiatric complications including seizures, confusion, and encephalitis, indicating that MPXV is able to invade the central nervous system (CNS) 7,10,[12][13][14][15] . Despite its severe manifestations, the underlying neuropathogenesis of mpox is unknown, and the susceptibility of different CNS cell types to MPXV infection has not been characterised.…”
Section: Main Textmentioning
confidence: 99%
“…From 1985 to 2021, serious neurological manifestations, including confusion, seizures and encephalitis, have been recorded in around 3% of MPXV infected patients 5 , including one fatal case 6 . Since May 2022, encephalitis has been diagnosed in several patients affected by MPXV infection [7][8][9][10][11][12][13][14] , including two young, healthy men that died following the complications 7 . Animal studies have suggested neuroinvasive potential of MPXV, detecting viral DNA in the brain of several rodent species [15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%